TNFα activation and TGFβ blockage act synergistically for smooth muscle cell calcification in patients with venous thrombosis via TGFβ/ERK pathway. Issue 16 (8th July 2022) - Wang, Penghui; Pan, Yiqing; Yang, Chenghao; Zhang, Linjie; Zhao, Zhen; Ye, Kaichuang; Li, Lei; Xia, Shoubing; Lu, Xinwu; Shi, Huihua; Li, Weimin; Yin, Minyi
Abstract: Venous calcification has been observed in post‐thrombotic syndrome (PTS) patients; yet, the cell types and possible mechanisms regulating this process are still unclear. We evaluated the calcium deposition within the venous wall, the cell type involved in the calcified remodelling of the venous wall after thrombosis and explored possible mechanisms in vitro. Calcium deposition was found in human specimens of superficial thrombotic veins and was co‐localized with VSMCs markers αSMA and TAGLN (also known as SM22α). Besides, the expression of osteogenesis‐related genes was dramatically changed in superficial thrombotic veins. Moreover, the inhibition of the TGFβ signalling pathway after TNFα treatment effectively induced the expression of osteogenic phenotype markers, the calcium salt deposits and the obvious phosphorylation of ERK1/2 and JNK2 in the VSMCs calcification model. Supplementing TGFβ2 or blocking the activation of the ERK/MAPK signalling pathway prevented the transformation of VSMCs into osteoblast‐like cells in vitro. Taken together, VSMCs have an important role in venous calcification after thrombosis. Supplementing TGFβ2 or inhibiting the ERK/MAPK signalling pathway can reduce the appearance of VSMCs osteogenic phenotype. Our findings may present a novel therapeutic approach to prevent of vascular calcification after venous thrombosis.